1998
DOI: 10.1001/archneur.55.5.726
|View full text |Cite
|
Sign up to set email alerts
|

New-Onset Psychogenic Seizures After Surgery for Epilepsy

Abstract: (1) Patients can develop new-onset psychogenic seizures after surgery for epilepsy. (2) Low full-scale IQ, serious preoperative psychopathologic conditions, and major surgical complications may be risk factors. (3) Atypical postoperative seizures should be evaluated with video electroencephalographic monitoring before concluding that they are epileptic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
1
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 14 publications
1
28
1
3
Order By: Relevance
“…In our sample of patients, however, we found that neurologic problems and epileptic seizures began at a significantly later age in postsurgical NES patients compared with other surgical patients. Similarly, we did not find evidence for the previously reported finding that patients who develop NESs after resective epilepsy surgery are more likely to have low intelligence or psychotic disorders (6). The NES patients in this study were comparable to or slightly higher than other surgical patients in terms of intellectual and social functioning.…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…In our sample of patients, however, we found that neurologic problems and epileptic seizures began at a significantly later age in postsurgical NES patients compared with other surgical patients. Similarly, we did not find evidence for the previously reported finding that patients who develop NESs after resective epilepsy surgery are more likely to have low intelligence or psychotic disorders (6). The NES patients in this study were comparable to or slightly higher than other surgical patients in terms of intellectual and social functioning.…”
Section: Discussioncontrasting
confidence: 98%
“…NESs are not infrequent among patients with well-documented chronic epilepsy (1)(2)(3). In several reported cases, NESs developed after resective surgery in patients with medically refractory epileptic seizures (4)(5)(6)(7).…”
mentioning
confidence: 99%
“…Seizure frequency has been reported to be high, and it is consistent with the pattern presented by our patient 2,4 .…”
Section: Discussionsupporting
confidence: 92%
“…The occurrence of de novo psychogenic seizures after epilepsy surgery is rare, and is estimated in 1.8% to 3.6% 2,4 . There are a few reports about its occurrence, with a total of 8 cases described in the literature 2,4-6 .…”
Section: Discussionmentioning
confidence: 99%
“…Two case series described the occurrence of psychogenic seizures after brain surgery, usually for epilepsy. 4,16 There have also been reports of conversion disorder after implantation of a spinal cord stimulator for pain. 3,11 To our knowledge, there is no reported case in the literature of conversion disorder in an operated brain tumour patient manifesting as transient monoplegia.…”
mentioning
confidence: 99%